A Feasibility Test of a Brief Mobile Virtual Reality Meditation for Frontline Healthcare Workers in a Hospital Setting - Tarrant, Jeff; Jackson, Ray; Viczko, Jeremy (Frontiers in Virtual Reality, 2022)
The purpose of this study was to examine whether a virtual reality plus neurofeedback (VR+NF) meditation experience (experimental condition) was more effective than a standard guided audio-only meditation (control condition) in improving mood in one hundred healthcare workers. Data collection occurred in a hospital setting between October, 2020 and March, 2021 at the height of the COVID-19 pandemic. Participants were alternately assigned to one of the two conditions. Before and after the meditation experience, participants completed the Brunel Mood Scale. Results indicated that both groups showed a similar and significant decrease in Anger, Tension, and Depression. On scales measuring Vigor, Fatigue, and Confusion, the VR+NF group showed decreases, while the audio-only group showed no significant change. The VR+NF group showed significant increases on the Calmness and Happiness scales, which did not change significantly in the audio-only group. These results suggest that the addition of VR and neurofeedback may increase the positive outcomes associated with standard audio-guided meditation. These increased benefits may be due to the sense of presence intrinsic to VR, the inclusion of nature-based scenes in the VR experience, as well as the increased self-awareness created by the addition of neurofeedback. As the pre and post measures take place within one 50-min session, further studies assessing the longer-term changes are needed.